Working principle of universal electric motor: educational reflection from an explanation of version type teaching series - Silva, Osmar Henrique Moura da (2013)
It is common the disclosure of a simple and low-cost version of an electric motor type series (or universal) for pedagogical purposes that can be quite profitable. However, due to their geometry and the arrangement of the coils, it is noticed a difficulty in determining the directions and the senses of the forces responsible for the rotor torque, resulting in incomplete or inadequate explanations for their operating principle. This difficulty is present indisclosures about this engine being further supported by revelations of investigated sample teachers who dedicated to study the experiment. Considering that, this study contributes to better clarify the origin of the rotational movement of the rotor didactic version of this engine in series adjusted by application of magnetic forces involved there. It ends with a reflection that raises awareness about the educational care about the physical explanations of the operation of electric motors in general.